Pengembangan Sistem Pengelolaan Surat berbasis Web memanfaatkan Teknologi Integrasi Protokol IMAP Gmail (Studi kasus: CV. Putra Bahari) - Dio Hilmi Habibi; Diah Priharsari; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Letters are written communication media that originate from one party and are addressed to other parties and are used to convey information. CV. Putra Bahari is a company engaged in the procurement of goods, services and construction services. The management of correspondence by CV. Putra Bahari currently uses conventional methods or has not been fully computerized, letters received and sent have different types, quantities and origins, including from gmail or from physical letters sent directly to the office of CV. Putra Bahari. That way, the use of correspondence management in the conventional way has many risks such as loss of mail data, takes up a lot of space and the process of managing correspondence such as distribution and making of letters. In filing letters, there are incoming and outgoing letters, where there are letters in the form of physical documents and soft files. With the above problems, it is necessary to develop a web-based mail management system to help manage correspondence with the integration of the IMAP Gmail protocol. Using the waterfall software development method because it has a sequential series and clear workflow. Where in the development stage using the waterfall method and designing using the Unified Model Language (UML) which consists of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. In its implementation, the Laravel framework is used which has the advantages of making a better program code function, has good documentation on the official page and provides security against basic web security attacks, while at the testing stage it uses black box testing.